Role Of Corporate Social Responsibility In Sustainable Development Of Society - Richa Srivastava (AG Volumes, 2021)
A large number of not-for-profit, social service, educational, health care, and environmental groups pitch half or full funding projects to corporations every year. Millions have been raised, and each one has been promised a return to the financing company. This means that each one has bottom-line measurements. Of course, the businesses who donate money and other resources do so because they believe they are doing something good for society as a whole. Consider the question of long-term viability. When it comes to corporate social responsibility (CSR), other names for it include "corporate conscience," "corporate citizenship," "social performance," and "sustainable responsible business." Corporate social responsibility (CSR) policy serves as a self-regulatory system for businesses to monitor and ensure that they are operating in accordance with legal and ethical standards, as well as with international norms and regulations. “Corporate social responsibility (CSR)” aims to inspire companies to accept responsibility for their actions and to have a beneficial effect on the environment, customers and workers as well as on the communities in which they operate.